La coordinación general como eje articular y los fundamentos técnicos del arquero en los niños de 8 a 10 años del Club Deportivo Especializado Formativo Macará F.C periodo 2016-2017 - Luzuriaga Gahona, Luis Miguel (2018)
This thesis entitled: THE GENERAL COORDINATION AS A JOINT AXIS AND THE TECHNICAL FOUNDATIONS OF THE ARCHER IN CHILDREN FROM 8 TO 10 YEARS OF THE SPECIALIZED SPORTS CLUB MACARÁ FC 2016-2017 PERIOD whose problem arises in how does the general coordination influence to facilitate the learning of the technical foundations of the goalkeeper in children from 8 to 10 years of the specialized sports club Macará F.C? as a general objective to carry out a series of methodological exercises to work on the technical foundations of soccer goalkeeper and general coordination in children from 8 to 10 years, from this work is proposed by means of two categories that are general coordination and the technical foundations of the soccer goalkeeper, the methodology represents the collection of information on the general coordination and technical foundations of the goalkeeper who will perform it in children from 8 to 10 years of the club located in the Macará Canton of the province of Loja. The resulting methodological proposal is given by an extensive analysis of the current situation by conducting surveys and applying tests, these instruments allowed observing the incidence of the exercises proposed in relation to the pre-test and post-test stage. Concluding that working in a programmed manner the specific exercises of the general coordination allowed the children to obtain a better execution of the technical foundations of the soccer goalkeeper. As a result of this research, a methodology has been achieved that allows to improve the coordinative capacities in the children and a good improvement to learn the technical foundations of the goalkeeper, developing good archers contributing to the children and the club.